The simmulation of reality. a critic of the reality show (2005)
Reality shows are one of the most successful television genres in the last few years. The exploration that this article will make around this genre consists of three parts. First, the tension that realities cause between representation as a traditional aesthetic style and simulation as an emergent aesthetic style will be examined. Second, the way realities participate in the construction of the world as image will be described. Finally, the article will explain the role that realities play in the contemporary aesthetic economy, and offer a socio-psychological explanation of its seductive power. The article approaches the study of reality shows by taking a critical perspective to the entertainment industry.